Design and Simulation of Slotted Antenna based on Vivaldi Antenna (International Journal of Scientific Research and Management (IJSRM), 2017)
Compact slotted patch antenna with a parasitic meander line is presented in this paper. There are two configuration of slotted Vivaldi antenna is presented. One is half slotted Vivaldi antenna and another one is full slotted Vivaldi antenna. Slotted Vivaldi antennas can be made for linear polarized waves or using two devices arranged in orthogonal direction – for transmitting / receiving both polarization orientations. This antenna is suitable for portable DVB-T which extended from 550 MHz to 950 MHz receiver applications and the WLAN (Wireless Local Area Network) IEEE 802.11b,g (5.1–5.8) GHz frequency bands and WiMAX band (3.3–3.8) GHz. The measured reflection coefficient of the proposed antenna is compared with the simulated one; good agreement is observed. Also, simulated radiation pattern of the antenna is presented. All simulations are carried out using the EM commercial simulator, high frequency structure simulator (HFSS)ver.13